Behavioural public sector accounting research in Indonesia: A literature review / Indrawati Yuhertiana - Yuhertiana, Indrawati (Accounting Research Institute (ARI) & Faculty of Accountancy, 2015)
The absence of a clear mapping of behavioural public sector accounting significantly motivates the conduct of this study. The role of behavioural accounting in accounting knowledge remains debatable despite the existence of widespread behavioural problems related to accounting and finance. Accordingly, a number of accounting articles published by the Indonesia National Symposium from 1999-2013 were reviewed to obtain an overview of the behavioural research development in the realm of accounting and financial administration. This study describes the behavioural phenomenon in government accounting in all stages of the state financial management cycle from budgeting planning to ratification, budget implementation, and accountability. The science of public sector accounting in Indonesia has developed along with the reform era, especially in terms of public sector reform since 2000.